Age‐related hearing loss: Why we need to think about sex as a biological variable. Issue 9 (18th June 2020) - Nolan, Lisa S.
Abstract: It has long been known that age‐related hearing loss (ARHL) is more common, more severe, and with an earlier onset in men compared to women. Even in the absence of confounding factors such as noise exposure, these sexdifferences in susceptibility to ARHL remain. In the last decade, insight into the pleiotrophic nature by which estrogen signaling can impact multiple signaling mechanisms to mediate downstream changes in gene expression and/or elicit rapid changes in cellular function has rapidly gathered pace, and a role for estrogen signaling in the biological pathways that confer neuroprotection is becoming undeniable. Here I review the evidence why we need to consider sex as a biological variable (SABV) when investigating the etiology of ARHL. Loss of auditory function with aging is frequency‐specific and modulated by SABV. Evidence also suggests that differences in cochlear physiology between women and men are already present from birth. Understanding the molecular basis of these sex differences in ARHL will accelerate the development of precision medicine therapies for ARHL.